Wear damage of out-of-round wheels in rail wagons under braking. (August 2019) - Lan, Qingqun; Dhanasekar, Manicka; Handoko, Yunendar Aryo
Abstract: Periodic deviation of the diameter of wheel across its circumference is referred to as the out-of-round (OOR) defect that can cause significant damages to wheel – rail interface, affect the service life of various components of the vehicle/track system and the safety of trains. Under braking, OOR defect may exacerbate these damages; to uncover such exacerbation, a multi-body dynamic simulation model in a fixed coordinate system for wagons containing new/ defect free or OOR wheels subject to braking torques has been formulated and validated using a dataset in the literature. Using the validated model, the effects of the repetition order (single or multiple deviations of diameter) of OOR defect and the severity of application of braking torques to wheel wear has been examined. It has been found that under constant speed, the normal contact force increased with the repetition order . The OOR defect dominated the normal contact force with a dynamic impact force factor of 1.48, whilst the new/ defect free wheels exhibited negligible impact force. It is shown that the effect of OOR defect is significant for wear of wheels under normal braking whist under wheel skid, braking torque dominates wear. Wheel unloading ratio is shown to be a better indicator for the determination of risk to derailment, than the commonly used Nadal's derailment quotient where the wheel contains OOR defect. Highlights: Out-of-round wheels under normal, severe and emergency braking investigated. A fixed coordinate model was formulated to investigate wheel skid under braking. Wheel-rail contact frictional power was used to determine wear depths. Wear under skid was significantly large irrespective of presence or absence of OOR. Unloading of OOR wheels better predict wagon derailment than Nadal's Criterion.